Business Model and Strategy Development of Commulus Digital Marketing and COmmunication Indonesia - Saputra, Arif Fajar; Motik, Suryani Sidik (The Indonesian Journal of Business Administration, 2013)
The findings of this study will help CIDMAC as new venture in digital advertising industry to formulate their business strategy (Especially in the beginning of their business) to be able to compete with existing competitors and capture many opportunities ahead. The authors propose the formulation of CIDMACâ€™s business model and DIAMOND Strategy as outlined in the implementation of business strategies in short term (1 year) and long term (3 years) that are expected to make CIDMAC business continues to grow and sustain in the long run. Moreover, the findings will give the latest overview of digital advertising in Indonesia.Â Keywords: Business Strategy, Indonesian Creative Industry, Digital Advertising Agency, Internet Marketing, Digital Marketing.